Effect of temperature on the photosynthetic efficiency and morphotype of Phaeocystis antarctica - Fraser Kennedy; Andrew McMinn; Martin, A (2012)
One of the only non-diatom species to dominate sea-ice assemblages is the haptophyte Phaeocystis antarctica . Here, the photosynthetic efficiency and morphotype expression of P. antarctica in response to freezing and melting in an artificial sea-ice habitat is investigated. Maximum quantum yield of photosystem II (Fv/Fm) was significantly different with respect to both light (light and dark, Two-way ANOVA, pb0.001) and depth within the ice (Two-way ANOVA, pb0.001). There was a decline in maximum quantum yield (Fv/ Fm) in cells at each level within the ice, but the decline was greater in the coldest part of the ice (i.e. close to the surface) than at the ice/water interface. Following the initiation of a melt cycle, Fv/Fm increased in both treatments, from 0.48±0.05 to 0.57±0.05 on day 10, and 0.38±0.06 to 0.44±0.07 on day 10, in the light and dark treatments respectively. The ice matrix induced solitary cell formation while melting induced colony formation. This change in morphology is not thought to reflect either temperature or nutrients but the physical presence of ice acting as a trigger for morphological change. This study utilised a novel ice tank technology to replicate sea-ice habitat and document the response of P. antarctica to freeze/thaw dynamics.